Caffeine-Containing Local Products and Their Effects on Liver and Kidney Histopathology: A Comparative Study - Javed, Anam; Rabia Manzoor; Muhammad Adnan; Ghulam Hayder; Muhammad Aqil; Saman , Gul e; Ashfaq, Gulshan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Caffeine has several modified natural and synthetic forms and it is the most abundantly consumed drug around the globe. It is present in fruits, seeds and leaves of many plants but coffee contains highest content of caffeine and is considered its richest source. It is also found in much high ratio in non-alcoholic beverages, i.e., tea and carbonated drinks like coke. The aim of current mammalian model based investigation was to evaluate the possible histopathological variations influencing the function of kidney and liver due to the intake of selective caffeinated products: Arabica and Robusta beans’ blend based coffee and coke. The 30 albino mice of male gender and 1.5 month age were acclimatized for ten days and later on, categorized as group I (control group which was treated with standard mice feed), experimental group II (treated with coffee blend) and experimental group III (treated with coke). The renal and hepatic histological sections were cut and stained for weekly observations. Hematoxyline and eosin staining was used and microscopic observations were recorded at 40X. The ANOVA based statistical analyses showed that significant variations occurred in body weight, diameter of renal blood vessels, glomeruli and of necrotic areas of both experimental groups (p ≤ 5%). Moreover in hepatic tissues, vein wall thickness, diameter of bile ducts and liver lobules also indicated significant variations. The conclusion is excessive and regular intake of above mentioned composition having coffee and coke may result in diverse physiological disturbances and a programmed general public awareness is required regarding their limited intake.